Institutionalizing the Concept of Legal Pluralism as an Effort to Realize Substantive Justice - Al Haq, Syaif; Pratama, Aditya Andel; Rozaan, Zaim; Sadiq, Muh. Fajar; Rukmini, Neng Vivie Nurfauziah (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
The concept of legal pluralism is a solution to the problem of diversity in a pluralistic country. Interestingly, although Indonesia recognizes diversity as the philosophical foundation of the life of the nation and state, the concept of legal pluralism has not been fully institutionalized. This article will explain, analyze, and explore the discourse of legal pluralism and substantive justice and explain the concept of institutionalizing legal pluralism in Indonesia as an effort to realize substantive justice for all Indonesian people. This research is a normative juridical research with conceptual, legislative, historical, and analytical approaches. The data of this research is literature data in the form of primary legal materials and secondary legal materials. The collection of legal materials is done through literature studies and analyzed using a qualitative approach with description and analysis techniques. The results show that legal pluralism not only allows recognition of the diversity of existing laws, but also has the potential to overcome the shortcomings of formal legal systems that tend to be homogeneous and less responsive to local contexts. The recommendation is for policy makers to reform the legal structure, legal substance, and legal culture that support the coexistence and interaction between various legal systems, so that substantive justice can be achieved through a more contextual and adaptive approach. The impact of institutionalizing legal pluralism is the realization of a strong legal pluralism system, a plural legal society, and substantive social justice for all Indonesian people.